RAPID ERUPTION OF SIBERIAN FLOOD-VOLCANIC ROCKS AND EVIDENCE FOR COINCIDENCE WITH THE PERMIAN-TRIASSIC BOUNDARY AND MASS EXTINCTION AT 251 MA - Kamo S.L.; Amelin Y.; Davis D.W.; Czamanske G.K.; Fedorenko V.A.; Trofimov V.R. (My University, 2003)
The Siberian flood-volcanic event is the most voluminous and explosive, continental, volcanic event known in the Phanerozoic record. U–Pb perovskite and zircon ages were obtained for lavas of the lowermost unit (251.7±0.4 Ma) and near-uppermost unit (251.1±0.3 Ma), respectively, of the volcanic sequence in the Maymecha–Kotuy area, Russia. Along with stratigraphic correlations and paleomagnetic evidence, these ages suggest that rapid extrusion of the entire ∼6500 m thick composite sequence occurred in less than 1 million years. The time of extrusion coincides precisely with an age of 251.4±0.3 Ma previously obtained for the Permian–Triassic mass-extinction event, the most devastating biotic crisis known. Emplacement of the Noril’sk–Talnakh ore-bearing intrusions, notable for their prodigious Cu–Ni–PGE deposits, was synchronous with these two major geologic events at 251.2±0.3 Ma. The Guli volcanic-intrusive complex in the Maymecha–Kotuy area appears to represent the final mafic magmatism of the entire Siberian flood-volcanic event. Baddeleyite from a carbonatite that intrudes the complex gives an age of 250.2±0.3 Ma, and shows possible 231Pa excess. The Bolgokhtokh granodiorite stock has a zircon age of 229.0±0.4 Ma, and represents the youngest known magmatism in the region.
Keywords: Triassic; Permian; Mesozoic::Triassic; Палеозой::Пермская; Paleozoic::Permian; Мезозой::Триасовая